(untitled) (Academia Science Repository, 2023)
The article contains a logical opinion about the crucial social basis of the development strategy of developing the intellectual potential of young people and human capital. Also, the reforms carried out in the field of higher education, the specific features of the training of talented personnel are socio-philosophically analyzed.